The 2010 International Joint Conference on Neural Networks (IJCNN) 2010
DOI: 10.1109/ijcnn.2010.5596528
|View full text |Cite
|
Sign up to set email alerts
|

Euclidean distance and second derivative based widths optimization of radial basis function neural networks

Abstract: The design of radial basis function widths of Radial Basis Function Neural Network (RBFNN) is thoroughly studied in this paper. Firstly, the influence of the widths on performance ofRBFNN is illustrated with three simple function approximation experiments. Based on the conclusions drawn from the experiments, we find that two key factors including the spatial distribution of the training data set and the nonlinearity of the function should be considered in the width design. We propose to use Euclidean distances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
3
0
3
Order By: Relevance
“…Con respecto a la distancia radial, esta es usada para la estimación de las desviaciones, que se calculan de tal manera que cada neurona de la capa oculta se active en una región del espacio de entradas con un solapamiento de las zonas de activación lo más ligero posible para suavizar la interpolación. Se aplica como distancia radial alguna de las distancias estadísticas definidas por [37] y [38], como la distancia euclidiana, de Mahalanobis, de Minkowski, de K. Pearson, de Canberra, de Clark, entre otras.…”
Section: Modelo Neuronal Artificialunclassified
See 1 more Smart Citation
“…Con respecto a la distancia radial, esta es usada para la estimación de las desviaciones, que se calculan de tal manera que cada neurona de la capa oculta se active en una región del espacio de entradas con un solapamiento de las zonas de activación lo más ligero posible para suavizar la interpolación. Se aplica como distancia radial alguna de las distancias estadísticas definidas por [37] y [38], como la distancia euclidiana, de Mahalanobis, de Minkowski, de K. Pearson, de Canberra, de Clark, entre otras.…”
Section: Modelo Neuronal Artificialunclassified
“…Las conexiones entre las neuronas de entrada a la capa oculta se hacen por medio de la función de Gauss definida en (1), de acuerdo con [40]. Las desviaciones a los centros son calculadas usando la distancia radial Euclidiana, definida en [37] y [38].…”
Section: Elaboración Entrenamiento Puesta En Marcha Y Validación Del Modelo Neuronalunclassified
“…Their experimental outcomes have shown that the nonsymmetric partition can lead to the development of more accurate RBF models, with a smaller number of hidden layer nodes. More elaborate methods have been suggested [58][59][60][61] for optimizing the RBF widths in order to improve approximation accuracy. Taking advantage of the linear connection between the hidden and output layer, most training algorithms calculate the synaptic weights of RBF networks by applying linear regression of the output of the hidden units on the target values.…”
Section: Orthogonal Least Squares (Ols)mentioning
confidence: 99%
“…This way, the best recognized RBFNN structure 11-88-1 gives good results. As discussed in previous section, and existing forecasting studies [7], [21]- [22] show that the conventional training procedure to train RBFNN rarely optimizes the training parameters of RBFNN. Hence, it is incapable to result in sufficiently accurate prediction.…”
Section: Radial Basis Function Neural Network (Rbfnn)mentioning
confidence: 99%